Realization of exact three-point difference schemes for nonlinear boundary-value problems on the semiaxis - Król, M.; Kutniv, M. V. (Ukrains’kyi Matematychnyi Zhurnal, 2016)
New algorithmic realization of exact three-point difference schemes via the three-point difference schemes of high order of accuracy is proposed for the numerical solution of boundary-value problems for systems of nonlinear ordinary differential equations on the semiaxis. We study the existence and uniqueness of the solution of three-point difference schemes and estimatie the rate of convergence. The results of numerical experiments are also presented.